2021
DOI: 10.1186/s13048-021-00890-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between the food security status and dietary patterns with polycystic ovary syndrome (PCOS) in overweight and obese Iranian women: a case-control study

Abstract: Background Polycystic ovary syndrome (PCOS), as one of the significant endocrine disorders, is common among women worldwide. Food insecurity (FI) and unhealthy dietary patterns can negatively affect reproductive health. The effects of the lifestyle modifications, especially dietary components, on PCOS are contradictory. The aim was the assessment of association between PCOS with food security status and dietary patterns among overweight or obese women. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 99 publications
1
6
0
Order By: Relevance
“…A cross-sectional study ( 42 ) reveals that women with higher levels of education have a significantly better understanding of PCOS compared to those with lower levels of education. Additionally, a case-control study ( 8 ) (n=240) finds that low socioeconomic status is associated with an increased risk of PCOS. Our work indicated that longer duration of education, higher educational attainment, and higher family income reduced the risk of PCOS, consistent with existing research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cross-sectional study ( 42 ) reveals that women with higher levels of education have a significantly better understanding of PCOS compared to those with lower levels of education. Additionally, a case-control study ( 8 ) (n=240) finds that low socioeconomic status is associated with an increased risk of PCOS. Our work indicated that longer duration of education, higher educational attainment, and higher family income reduced the risk of PCOS, consistent with existing research.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there are observed connections between dietary imbalances and PCOS ( 7 ). In addition, socioeconomic factors, such as educational levels and family income, have been shown to impact PCOS awareness and may increase the risk of PCOS through pathways influencing lifestyle choices ( 8 ). Therefore, elaborating on the clear causal effects of lifestyle and social economy on PCOS is helpful for society to coordinate medical resources and macro-control the incidence of PCOS by analyzing the regional economy and lifestyle, ultimately alleviating the social burden.…”
Section: Introductionmentioning
confidence: 99%
“…The balance of AEs and AEEs plays important roles in physiological functions [ 16 ]. Previous studies have indicated that AEs and AEEs are associated with female reproductive health [ 19 , 23 , 20 22 ]. However, at present, no studies have reported on the effect of AEs and AEEs on the ovarian reserve.…”
Section: Discussionmentioning
confidence: 99%
“…The potassium (K + ) channel has important effects on reproductive health outcomes, and can be involved in outcomes such as malformation of the fallopian tube [ 36 ], and male infertility [ 37 ]. A population study reported that women with PCOS had a lower potassium intake than women in a control group [ 19 ]. Whether K plays a role in the ovarian reserve remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation